2020
DOI: 10.1111/1365-2745.13485
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐off between standing biomass and productivity in species‐rich tropical forest: Evidence, explanations and implications

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 91 publications
0
11
0
1
Order By: Relevance
“…We are aware that taller tree species have a higher basal area at the stand level (Kohyama et al, 2020). The applied standardization of recruitment rates per basal area might thus have introduced an artefactual negative correlation between stature and per-basal area recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that taller tree species have a higher basal area at the stand level (Kohyama et al, 2020). The applied standardization of recruitment rates per basal area might thus have introduced an artefactual negative correlation between stature and per-basal area recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, RAWP decreases across tree size classes, consistent with our expectations (Hypothesis 2a), with previous findings in tropical and temperate forests (Mencuccini et al ., 2005; Kohyama et al ., 2020), and with the expected decrease in photosynthetic activity (per unit mass; Drake et al ., 2010; H. Poorter et al ., 2015) and increase in nonwoody tissue investment (Ryan et al ., 2004; Thomas, 2011) as trees get larger. This pattern was surprisingly similar across all our sites.…”
Section: Discussionmentioning
confidence: 93%
“…Studies across many different forest types and tree species have observed decreasing productivity per unit biomass with tree size (e.g. Mencuccini et al ., 2005; Kohyama et al ., 2020). This occurs even though absolute productivity generally continues to increase with tree size (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Большое количество статей отнесено ко второй группе: потоки углерода в надземной фитомассе [17][18][19][20][21][22][23][24][25], часть из которых посвящено балансу углерода экосистем умеренных лесов, преимущественно на примере о. Хоккайдо [23; 26], часть -мангровым лесам [5; 7; 27-29], а также луговым сообществам, grasslands [9; 30].…”
Section: результатыunclassified